Development of wordwall educational games based on Peo-Heda local wisdom to improve children's social skills - Konstantinus Dua Dhiu; Wilibaldus Bhoke (Harmoni Sosial: Jurnal Pendidikan IPS, 2025)
This research aims to develop the GAULL (Wordwall Educational Game) Puzzle Application, based on the local culture of Woe Are "PEO–HEDA", as an educational medium that can improve early childhood social skills. The study's background reveals that children's social skills, particularly in terms of cooperation, empathy, communication, and conflict resolution, remain relatively low. In fact, these social values are the foundation of children's social development, and interaction through collaborative play can accelerate the development of social cooperation. This research employs the R&D method, utilising the ADDIE model, which encompasses the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were 22 children aged 5–6 years at Satap SDK Olabolo Kindergarten, Golewa District, Ngada Regency. Application development is carried out using the Wordwall platform, which incorporates puzzle games to support contextual learning. The results of the material expert's validation gave a score of 32 (in the very feasible category), while the media expert and design expert gave scores of 40.5, which also indicate very high feasibility. These results suggest that GAULL fulfils the technical and pedagogical aspects as a learning medium that is in accordance with the characteristics of early childhood social development. Findings in the field show that the use of GAULL has a positive impact on improving children's social skills. Children exhibit more active interaction when sharing, participating in group tasks, and demonstrating empathy and cooperation while using the GAULL application.